Constraints and opportunities of raw jute production: a household level analysis in Bangladesh - Sheheli, S; Roy, B (Progressive Agriculture, 2015)
The study was conducted to investigate the existing status and practices of jute cultivation. A total of 100 farmers were interviewed by using a structured interview schedule from two villages (Damor and Nathpara) of Kishoregonj sadar upazila of Kishoregonj district at their houses and/or farm sites during April to June 2014. The study confirmed that most farmers have improved their socio-economic conditions through jute cultivation. The impact analysis of jute cultivation on livelihood of jute farmers shows that overall 61% jute farmers have increased overall livelihood from jute cultivation during the last four years (2011-2014). Deshi variety of jute has been widely grown across the region due to its wider adaptability and quality fiber. Jute area has been increased and some rice field has been replaced by jute due to its high demand in country. In addition, farmers are motivated to cultivate jute. But study revealed that productivity ranged from 750 kg to 1022 kg per hectare that are lower than other jute growing areas of Bangladesh. Average cost of production of fiber was estimated at Tk 15/kg. The study indicates that the maximum production cost has involved in fiber extraction (20%) and weeding (20%). The study also revealed that lack of quality seed, high cost of jute production, lack of training facilities, inadequate credit facilities, high disease infestation, high price of inputs, unstable jute price, shortage of labor at peak period, lack of retting water and weed problem were the main constraints in jute production and processing. For the sustain of jute cultivation in the study area, it would be better to provide subsidies on seeds and fertilizer to jute farmers thereby profit margin becomes high and will encourage growers in producing more raw jute within the country for the fulfillment of raw jute requirement of local jute industries. Cost effective technologies have to be developed in jute production and processing aspects for lowering the production cost and increasing the profit margin. Progress. Agric. 2014. 25: 38-46